Short-stop visitation in Shark Bay World Heritage Area: an importance–performance analysis. Issue 1 (2nd January 2017) - McGuiness, Vanessa; Rodger, Kate; Pearce, Joanna; Newsome, David; Eagles, Paul F.J.
ABSTRACT: An importance–performance analysis (IPA) investigated levels of satisfaction with natural attributes and facilities in place at a short-stop nature-based tourism site in the Shark Bay World Heritage Area (WHA). Over 700 on-site questionnaires were collected from visitors who visited the stromatolite viewing-boardwalk, an attraction with little managerial presence in the Hamelin Pool Marine Nature Reserve. Results indicate that, although an attraction in its own right, visitors use the Reserve as a 'convenient break' en route to other destinations in the WHA. Visitors indicated high interest in the natural attributes and the interpretive educational facilities at the site and are overall satisfied with their experience, despite low levels of visitor infrastructure and facilities. This study found that acceptable levels of visitor satisfaction can occur at short-stop sites with minimal levels of infrastructure. Visitors identified the need for additional educational facilities, with a preference for updating interpretative signs or developing an educational mobile phone app. In addition, this research emphasises the IPA approach as a useful tool for identification of management priorities for infrastructure and programme development, prior to implementing management change of a site.